PERIODONTOPROTECTIVE EFFECT OF NIMESULIDE AND NaHS UNDER SIRS CONDITIONS - Tkachenko O.T.; Pletnov V.V.; Mykytenko A.O. (Biotechnologia Acta, 2025)
Hydrogen sulfide donors can protect the gastric mucosa from nimesulide damage, but their combined effect is unknown.